Early Spatial Memory Impairment in a Double Transgenic Model of Alzheimer's Disease TgF-344 AD - Proskauer Pena, Stephanie L; Mallouppas, Konstantinos; Oliveira, Andre M G; Zitricky, Frantisek; Nataraj, Athira; Jezek, Karel (Brain sciences, 2021)
Before the course of Alzheimer's disease fully manifests itself and largely impairs a patient's cognitive abilities, its progression has already lasted for a considerable time without being noticed. In this project, we mapped the development of spatial orientation impairment in an active place avoidance task-a highly sensitive test for mild hippocampal damage. We tested vision, anxiety and spatial orientation performance at four age levels of 4, 6, 9, and 12 months across male and female TgF-344 AD rats carrying human genes for presenilin-1 and amyloid precursor protein. We found a progressive deterioration of spatial navigation in transgenic animals, beginning already at the age of 4 months, that fully developed at 6 months of age across both male and female groups, compared to their age-matched controls. In addition, we described the gradual vision impairment that was accentuated in females at the age of 12 months. These results indicate a rather early onset of cognitive impairment in the TgF-344 AD Alzheimer's disease model, starting earlier than shown to date, and preceding the reported development of amyloid plaques.
Keywords: spatial memory; Alzheimer’s disease; navigation; TgF-344 AD